Code Switching and Code Mixing in Negeri Para Bedebah Novel - Risweni; I Gusti Agung Sri Rwa Jayantini; Ni Made Verayanti Utami (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
The phenomenon of code switching and code mixing is one of the various social contexts that can help in interaction and communication process, from one language to another, especially Indonesian-English. The study concerns are an attempt to understand the code switching and code mixing in the novel Negeri Para Bedebah by Tere Liye. The study uses the discriptive qualitative research method. It means that it describes clearly the fact of code switching and code mixing  based on the data that gained through reading the whole contain of the novel. The data was taken from episodes 23 until episodes 48 in the novel Negeri Para Bedebah by Tere Liye. The method used in collecting the data is library research method. The researcher reads the novel intensively to find out the data that suitable with the study and observing the utterance produced by the characters in the novel. For analyzing the data researcher applying the theory by Hoffmann (1991) and Muysken (2000). The result concludes code switching intention of clarifying the speech content for interlocutor and code mixing congruent lexicalization is dominantly used by the characters with 46,03% and 48,80%. Meanwhile, code switching quoting someone's word and type code mixing alternation be the lowest with 0,80% and 1,60%.